PENGARUH PENDIDIKAN, KESEHATAN DAN GENDER TERHADAP TINGKAT KEMISKINAN DI PROVINSI NUSA TENGGARA TIMUR - Reky Oktavian Fikri; Agustina Suparyati (Media Ekonomi, 2017)
The purpose of this study is expected to analyze how and how big the influence of education variables (RLS), health variables (AHH) and gender variables (TPAK) to poverty in East Nusa Tenggara, so it is expected to be used as one the basis for determining poverty reduction policy in East Nusa Tenggara. While the method of analysis used in this research is linear regression data panel with Fixed Effect Method and with the help of software eviews 9. The data used in this study are secondary data obtained from BPS and East Nusa Tenggara Book In Number as support. The results of this study indicate that educational variables (RLS) significantly and negatively correlated to poverty rate, health variables (AHH) significantly and negatively correlated to poverty rate and gender variables (TPAK) have no significant effect and negative correlation to poverty rate in East Nusa Tenggara.